Isu Bencana dan Prinsip-Prinsip Humanitarian Dalam Studi Ilmu Hubungan Internasional - Anita Afriani Sinulingga (Department of International Relations, Universitas Andalas, 2016)
This article seeks to explore how the issue of disaster and humanitarian principles applied in International Relations’ studies. This article will be shaped into two parts. The first section will describe the disaster issues in International Relations’ studies. This section will explain how tol ink disaster issues in international relations and the application of disaster issues that may be developed in International Relations’ studies. The second part will describe the development of Humanitarian principles derived from the Geneva Convention. In the convention, there are four humanitarian principles as the basis of any humanitarian action, but these principles need to be so that it can operasionalize in International Relations’ studies.Keywords: disaster, humanitarian, International Relations’ studies